Spatial assessment of erosion and landslide hazards as indicators of land degradation in Solok Regency, West Sumatra - Dasrizal, Dasrizal; Juita, Erna; Wilis, Ratna; Febriandi, Febriandi; Febriani, Trina (Brawijaya University, 2026)
This study conducted an integrated spatial assessment to identify and map erosion and landslide threats, determining high-risk degraded areas in Solok Regency. The methods combined the Universal Soil Loss Equation (USLE) and the Analytic Hierarchy Process (AHP) within a Geographic Information System (GIS) framework. The analysis revealed a critical disconnect between erosion and landslide risks. Although 52.1% of the total area (?101,500 ha) was classified as safe from erosion (EHI<1), a substantial portion of this “safe” land-39.4% and 6.94% of the total area, respectively, exhibited moderate to high landslide susceptibility. Conversely, within the 37.1% of the area unsafe from erosion (EHI>1), moderate and high landslide susceptibility covered 24.3% and 7.4% of the total area, respectively. These results demonstrated that landslide triggers are independent of surface erosion processes in many areas, often occurring in locations considered